QUALITY OF LIFE OF THE ELDERLY IN THE RURAL REGION OF DELHI, INDIA - Yadav, Ankit; Meena, G. S.; Sharma, Nandini; Kumar, Rajesh (Universitas Airlangga, 2025)
Introduction: The proportion of elderly people in India has sharply increased. According to World Population Prospects 2019, the elderly population will be around 19% by 2050. Due to this, there remains a concern about the quality of life (QOL) of the elderly. There is a scarcity of knowledge about QOL and related factors influencing the elderly population, particularly in rural areas of northern India. So, this study was conducted. Aims: To study the quality of life in the elderly aged sixty years and above using WHOQOL-BREF in rural Delhi. Methods: Cross-sectional study in the community. People aged 60 and older in the study area were enrolled using simple random sampling. A total of 195 elderly people were enrolled in the study after obtaining consent. The data was imported into MS Excel and evaluated with SPSS version 25. For descriptive and inferential statistics, p-values of 0.05 were deemed statistically significant. Results: Among the 195 participants, 40.5% were men and 59.5% were women. The proportion of married elderly was 47.7% while the rest were widowed, and 47.2% of the elderly were illiterate. Out of 195 participants, 155 were living in a joint family. Physical health (60.76±11.31), Psychological (67.90±8.71), Social relationship (90.81±12.31), and Environment domain (83.23±11.59) had the highest mean WHOQOL-BREF scores. Conclusions: The QOL score was highest in the social relationship category and lowest in the physical health category. Researchers can conduct a qualitative study in the future to determine the factors affecting quality of life.